Intermediate and Advanced ESL Speakers’ Pause and Repair Use in the Finnish National Certificate of Language Proficiency Speaking Test: A mixed methods study - Kim, Tytti (My University, 2021)
This thesis examined intermediate and advanced ESL speakers’ pause and repair use in the Finnish National Certificates of Language Proficiency speaking test, combining quantitative and qualitative research methods in an attempt to answer the following research questions: “Which quantitative measures of fluency distinguish between intermediate and advanced levels of proficiency?”; “how do pause and repair use distinguish between intermediate and advanced levels of proficiency?”; and “are pause and repair use interdependent?” 30 intermediate and 30 advanced Finnish L2 speakers taking a proficiency test in English were sampled from the Finnish National Certificates of Language Proficiency corpus (YKI corpus) and controlled for age, gender, and level of education. Their speech samples were transcribed, annotated, and analysed statistically. The quantitative results attained by analysing extreme cases showed that the temporal fluency measures of articulation rate, mean length of run, pause duration, frequency, and location as well as repair location distinguished between the intermediate and advanced levels of YKI, and that the largest difference between the two groups was in the mean lengths of run, which was used for extreme case sampling. These extreme samples from 12 participants were then analysed quantitatively for pause and repair use based on Nakatsuhara, Tavakoli & Awwad’s typology (2019): pauses and repairs were divided into pauses and repairs related to access and retrieval difficulty, reformulations, and effective speech delivery. Qualitative results showed that while intermediate participants had slightly more pauses and repairs related to access and retrieval difficulty than advanced participants, advanced participants were successful in their lexical and structural search more often than intermediate participants. In contrast, intermediate participants had more pauses related to reformulations than advanced. As for repairs, both intermediate and advanced participants had comparable numbers of reformulation repairs, but reformulation repairs were more common in the speech of intermediate and advanced participants with low mean lengths of run. In addition, the results showed that advanced participants used more of their pause and repair opportunities for more effective delivery. Advanced participants also used pauses and repairs to navigate socially and culturally difficult topics. Finally, the results showed that pause and repair use are interconnected: pause and repair use co-occurred and were used to achieve similar effects. The results suggest that pause and repair use, based on which inferences of L2 speakers’ cognitive fluency can be made, should not be overlooked in fluency studies or proficiency testing. It is suggested that pause and repair use should be studied further and included into definitions and operationalisations of L2 fluency.
Keywords: second language fluency, Finnish national certificates of language proficiency, YKI, L2 proficiency, language testing, L2 English, English as a Second Language